Factors associated with the catastrophic decline of a cloudforest frog fauna in Guatemala - Mendelson III, J R (2004)
Comparison of recent and historical surveys of frog populations in cloudforest habitat in Sierra de las Minas, Guatemala, indicated population declines and local extirpation of several species. Pathological exams of diseased tadpoles indicated infection by amphibian chytridiomycosis. The local habitat has been severely altered by recent establishment of large-scale leatherleaf fern production. Analysis of water chemistry at our study site suggested increased nitrogenation associated with the leatherleaf industry.